Impact of Shifting Cultivation on Litter Accumulation and Properties of Jhum Soils of North East India - Sapu Changkija; Samarendra Hazarika, Henry Saplalrinliana, Dwipendra Thakuria (Journal of the Indian Society of Soil Science, 2017)
This study assessed whether the slash-burn practice (jhum) induced disturbance on the above-ground biological inputs (plant biomass and forest floor litters, FFLs) had any influence on the soil processes in terms of soil enzyme activities. The jhum cycles of 5, 10 and 15 years from Mizoram and 5, 10 and 20 years from Nagaland were considered. Litter (adjacent fallow phase/secondary forest) and soil samples (burnt and unburnt cropping phases) were collected from three slopes (summit, shoulder and backslope) from each site and were analyzed for soil physicochemical and biochemical properties. Accumulation of FFLs increased significantly with the increasing length of fallow phase and accumulation dynamics showed an increasing trend in the order January > April > August > November. Values of bulk density (BD), pH, electrical conductivity (EC), avail-P and avail-K in soils under burnt sites were found higher relative to their values in unburnt sites and the reverse trend was true in case of soil organic carbon (SOC) and avail-N. Except BD, values of these soil properties were significantly higher in the longer fallow phase compared to that in shorter fallow phase (P<0.05, Kruskal-Wallis test). The activity of soil enzymes viz. amylase (AMY), b-glucosidase (GSA), dehydrogenase (DHA), aryl-sulphatase (ASA), acid-phosphatase (PHA) and protease (PRO) were differed significantly between burnt and unburnt or among fallow phases (P<0.05, Kruskal-Wallis test). The activities of DHA, GSA, PRO and PHA in burnt soils were decreased, whereas ASA activity increased relative to unburnt soils. Activities of AMY, GSA, DHA, ASA, PHA and PRO were significantly higher in longer fallow phase than that in shorter fallow phase. In exception under burnt condition, AMY and GSA activities were significantly lower in longer fallow phase than that in short fallow phase. In conclusion, burning of biomass releases a higher quantum of plant available nutrients in jhum soils momentarily, which can support better crop growth under longer fallow lengths. However, burning practice negatively impacted the biochemical processes of jhum soils indicating a gradual decline in the inherent nutrient cycling potentials of soils under jhum cycles.